2017
DOI: 10.1016/j.rbmo.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive preimplantation genetic screening using array comparative genomic hybridization on spent culture media: a proof-of-concept pilot study

Abstract: The aim of this pilot study was to assess if array comparative genomic hybridization (aCGH), non-invasive preimplantation genetic screening (PGS) on blastocyst culture media is feasible. Therefore, aCGH analysis was carried out on 22 spent blastocyst culture media samples after polar body PGS because of advanced maternal age. All oocytes were fertilized by intracytoplasmic sperm injection and all embryos underwent assisted hatching. Concordance of polar body analysis and culture media genetic results was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 40 publications
2
75
2
1
Order By: Relevance
“…Nonetheless, blastocentesis entails some degree of invasiveness to the embryo, although it is minimal. To develop a completely noninvasive, inexpensive, and easily implementable methodology for PGT purposes, several investigators proposed the use of spent culture medium collected at blastocyst stage (SBM) as a source of embryonic DNA (15)(16)(17). In particular, Xu et al (18) have shown high ploidy concordance rate between SBM samples and their corresponding embryos (>80%).…”
mentioning
confidence: 99%
“…Nonetheless, blastocentesis entails some degree of invasiveness to the embryo, although it is minimal. To develop a completely noninvasive, inexpensive, and easily implementable methodology for PGT purposes, several investigators proposed the use of spent culture medium collected at blastocyst stage (SBM) as a source of embryonic DNA (15)(16)(17). In particular, Xu et al (18) have shown high ploidy concordance rate between SBM samples and their corresponding embryos (>80%).…”
mentioning
confidence: 99%
“…The sample size ranged from seven (Shamonki et al, 2016;Liu et al, 2017) to 70 (Hammond et al, 2017) couples undergoing assisted reproductive technology procedures. Gamete fertilization was carried out mainly by intracytoplasmic sperm injection (ICSI) (86.7% [13 out of 15]) (Stigliani et al, 2013;Wu et al, 2015;Shamonki et al, 2016;Xu et al, 2016;Feichtinger et al, 2017;Hammond et al, 2017;Liu et al, 2017;Yang et al, 2017;Capalbo et al, 2018;Ho et al, 2018;Kuznyetsov et al, 2018;Li et al, 2018;Vera-Rodriguez et al, 2018) and the other two studies did not report the fertilization method Galluzzi et al, 2015). In 86.6% (13 out of 15) of studies, Cf-DNA from SCM alone was evaluated (Stigliani et al, 2013;Assou et al, 2014;Galluzzi et al, 2015;Wu et al, 2015;Shamonki et al, 2016;Xu et al, 2016;Feichtinger et al, 2017;Liu et al, 2017;Capalbo et al, 2018;Ho et al, 2018;Vera-Rodriguez et al, 2018), whereas a mixture of SCM and blastocoel fluid was assessed in 26.7% (four out of 15) of them (Hammond et al, 2017;Yang et al, 2017;Kuznyetsov et al, 2018;Li et al, 2018).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The characteristics of the embryos associated with each SCM sample were also heterogeneous. Specifically, 93.3% (14 out of 15) studies evaluated cf-DNA released from fresh embryos (Stigliani et al, 2013;Galluzzi et al, 2015;Wu et al, 2015;Shamonki et al, 2016;Xu et al, 2016;Hammond et al, 2017;Liu et al, 2017;Yang et al, 2017;Feichtinger et al, 2017;Capalbo et al, 2018;Ho et al, 2018;Kuznyetsov et al, 2018;Li et al, 2018;Vera-Rodriguez et al, 2018), and 20.0% (three out of 15) of studies Kuznyetsov et al, 2018;Ho et al, 2018) assessed cf-DNA secreted from cryopreserved embryos. Moreover, embryo micromanipulation, e.g.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the blastocoele fluid truly represents the chromosome complement of the whole embryo still needs to be demonstrated; however, this is an interesting research avenue as blastocysts completely recover and regain their original morphology after biopsy, and blastocoele aspiration is therefore considered to be less invasive than blastocyst biopsy [32]. Analysis of the culture medium in which the embryo was cultured is non-invasive, although here there are reasonable doubts whether the DNA present in the medium is coming from the embryo [33][34][35].…”
Section: Blastocyst Biopsymentioning
confidence: 99%